Początki ewangelizacji Islandii - Adamiak, Grzegorz (Annales Missiologici Posnanienses, 2019)
The turning point of Icelandic history was the reception of Christianity. After the discovery of the island, and then its settlement and the organization of an independent state, this was another step in the unification of the Icelandic nation. The circumstances of Iceland's acceptance of Christianity are peculiar in comparison with other countries in Europe at that time. While the decision to accept a new religion was usually made by the ruler, in Iceland the introduction of Christianity took place by the decision of the pagan parliament. Opposition to each other, the pagan and Christian factions, through reasonable negotiations, agreed in a bloodless manner on political agreement in this matter. The national assembly – Althingi – made a resolution in the summer of 1000 establishing a Christianity valid for the whole country religion. It is worth noting that pagan priest and clan leader Thorgeir Thorlaksson, played a crucial role here. Iceland was thus a country that was an exception to the European countries, which accepted a new faith through the conscious and voluntary decision of its inhabitants.